Code-Switching and Code-Mixing in Windah Basudara’s Roblox Gameplay - Artika Shitta Ramadani; Destia Puspitawati; Nur Hanifa Fitri Oktavianti; Teguh Sarosa (LingPoet: Journal of Linguistics and Literary Research, 2026)
This study examines Windah Basudara's multilingual practices in his Roblox gaming livestream, "AKU MENDAKI GUNUNG SUNDA INDONESIA DI ROBLOX… Mount Sunda.". Using a descriptive qualitative approach, the study identifies and analyzes the various types and communication roles of code switching, code mixing, and slang that arise throughout the webcast. The data were gathered through observation, transcription, and contextual note-taking, then evaluated utilizing an interactive model of data reduction, display, and conclusion drawing. The data show that insertion is the most common type of language mixing, demonstrating how English gaming terminology becomes deeply embedded in Indonesian digital communication. Intra-sentential switching and congruent lexicalization are also common, demonstrating Windah's strong bilingual fluency and spontaneous language output. These findings emphasize how Indonesian gamers creatively. These multilingual activities serve number of communicative purposes, such as expressing feelings, keeping viewers interested, organizing group activities, and fostering closer relationships with viewers. The livestream's expressive and participatory qualities are further enhanced with slang and multimodal components, including intonation, visual signals, and sound effects. Overall, the study reveals that multilingualism in gaming livestreams is not random but driven by communicative demands, emotional expressiveness, and the dynamic rhythm of games. blend languages to form identity, build solidarity, and navigate real-time digital interaction.